(untitled) (Eureka Journal of Humanities and Social Research, 2026)
This article reveals the process of the First and Second Renaissance that took place in our country in the IX–XII and XIV–XVI centuries, the reasons for its emergence, the scientific heritage of the scholars who lived during these periods, and how this serves as a foundation for the “New Uzbekistan” and the “Third Renaissance,” the implementation of which has been set as a goal today.